Studi Kasus Kerajinan Tenun Silungkang di Toko Fauzan di By Pasa Ketaping - Restati Nursadi; Yahya Yahya (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Silungkang weaving is a traditional heritage of the Silungkang community, long recognized in Sawahlunto. However, this tradition is currently under threat due to the lack of younger generations continuing it, with the majority of artisans being over 40 years old. This study aims to analyze the existence and development of Silungkang weaving in Padang City, particularly concerning its products, motifs, colors, and weaving techniques. The research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that the interest of the younger generation in Silungkang weaving is very low, while the remaining artisans continue to use traditional tools and ancestral motifs. However, there has been some development in more varied motifs that are no longer confined to the old designs. The basic weaving techniques used also show variations from simple to more complex songket techniques. The conclusion of this study emphasizes the importance of preservation efforts and innovation so that Silungkang weaving can continue to survive and evolve in the future.